A (in)visibilidade da cultura surda no contexto escolar do Centro Territorial de Educação Profissional Piemonte do Paraguaçu I de Itaberaba-Bahia - Rodrigues, Isis Monteiro (2018)
This dissertation, entitled "The (in)visibility of the deaf culture in the school context of the Territorial Center of Professional Education of Piedmont of Paraguaçu I of Itaberaba-Bahia", aims to analyze how the school space has been perceiving and considering the different cultures existing in its context, specifically the deaf culture, and seek to contribute to the process of positivation of the deaf identity and the affirmation of its cultural specificities in educational practices. The theoretical basis of this research is based on studies on deafness, deaf culture, cultural artifacts, critical multiculturalism, Cultural Studies and Deaf Studies, with contributions in Batista and Canen, Costa, Hall, Kelman, McLaren, Perlin, Quadros, Rosa, Sá, Skliar, Strobel, among others. The research, with a qualitative approach, inspired by ethnography, had as subjects studied deaf students, teachers, translators and sign language interpreters, pedagogical coordinator and the director of the researched school. The instruments used for the construction of data were the semi-structured interview and participant observation. I also used the field diary and photographs. The results of the research indicated that the cultural artifacts of the deaf, such as sign language, visual experience and the visual arts, aregenerally not considered by the school. Thus, the first artifact, sign language, is partially envisaged, used only by deaf students and translators and interpreters of sign language at the school. The second artifact is contemplated in some projects developed by the school, but it is not part of the practices of all teachers studied. Already the third artifact, only inserted in the extra class activities of the school institution. Thus, it is concluded that the deaf culture has little visibility in the researched school. Thus, it is necessary to adopt some fundamental measures for the affirmation and permanence of the deaf culture in the school space, such as: moments of sensitization of the hearing professionals of the school on deafness and its specificities; socialization of LIBRAS at school so that communication with deaf students is not restricted to sign language translators and interpreters; extension of the cadre of sign language translators and interpreters so that the deaf are assisted in all classes; clarification on the role of TILS; investment in training teachers to work in the area of deafness, so that they know the peculiarities of this and contemplate in the methodological field and in the elaboration of projects that take into account the visual, linguistic and artistic peculiarities of the deaf. Finally, projects that favor the deaf culture, giving it greater relevance and visibility in school.